Engineering lithoheterotrophy in an obligate chemolithoautotrophic Fe(II) oxidizing bacterium - Jain, Abhiney; Gralnick, Jeffrey A. (Scientific reports, 2021)
Neutrophilic Fe(II) oxidizing bacteria like Mariprofundus ferrooxydans are obligate chemolithoautotrophic bacteria that play an important role in the biogeochemical cycling of iron and other elements in multiple environments. These bacteria generally exhibit a singular metabolic mode of growth which prohibits comparative “omics” studies. Furthermore, these bacteria are considered non-amenable to classical genetic methods due to low cell densities, the inability to form colonies on solid medium, and production of copious amounts of insoluble iron oxyhydroxides as their metabolic byproduct. Consequently, the molecular and biochemical understanding of these bacteria remains speculative despite the availability of substantial genomic information. Here we develop the first genetic system in neutrophilic Fe(II) oxidizing bacterium and use it to engineer lithoheterotrophy in M. ferrooxydans , a metabolism that has been speculated but not experimentally validated. This synthetic biology approach could be extended to gain physiological understanding and domesticate other bacteria that grow using a single metabolic mode.